2023
DOI: 10.1186/s40001-023-01190-8
|View full text |Cite
|
Sign up to set email alerts
|

Schisandrin A regulates the Nrf2 signaling pathway and inhibits NLRP3 inflammasome activation to interfere with pyroptosis in a mouse model of COPD

Abstract: Chronic obstructive pulmonary disease (COPD) is a serious chronic lung disease. Schisandrin A (SchA) is one of the most important active ingredients in Schisandra chinensis and has been used to treat various lung diseases in several countries. Here, we studied the pharmacological effect of SchA on airway inflammation induced by cigarette smoke (CS) and explored the therapeutic mechanism of SchA in COPD model mice. Our results showed that SchA treatment significantly improved the lung function of CS-induced COP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(1 citation statement)
references
References 51 publications
0
1
0
Order By: Relevance
“…Schizandrin A and schizandrin B are both active lignan metabolites extracted from the botanical drug Schisandra chinensis (Turcz.) Baill with antioxidant and antitumor effects ( Xiang LB et al, 2023 ; Zeng J et al, 2023 ). Pu H et al (2021) found that schizandrin A (10, 20, 30, 40, 50 μg/mL for 24, 48, 72 h) was able to upregulate the expression of p-PERK, p-eIF2α, and CHOP in GES-1 and AGS cells, inhibiting GC cells’ viability and inducing apoptosis, which could be reversed by the ERS inhibitor 4-PBA.…”
Section: Chinese Botanical Drug Extracts Against Digestive System Tum...mentioning
confidence: 99%
“…Schizandrin A and schizandrin B are both active lignan metabolites extracted from the botanical drug Schisandra chinensis (Turcz.) Baill with antioxidant and antitumor effects ( Xiang LB et al, 2023 ; Zeng J et al, 2023 ). Pu H et al (2021) found that schizandrin A (10, 20, 30, 40, 50 μg/mL for 24, 48, 72 h) was able to upregulate the expression of p-PERK, p-eIF2α, and CHOP in GES-1 and AGS cells, inhibiting GC cells’ viability and inducing apoptosis, which could be reversed by the ERS inhibitor 4-PBA.…”
Section: Chinese Botanical Drug Extracts Against Digestive System Tum...mentioning
confidence: 99%